2021
DOI: 10.3390/ijms221910372
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic GMP in Liver Cirrhosis—Role in Pathophysiology of Portal Hypertension and Therapeutic Implications

Abstract: The NO-cGMP signal transduction pathway plays a crucial role in tone regulation in hepatic sinusoids and peripheral blood vessels. In a cirrhotic liver, the key enzymes endothelial NO synthase (eNOS), soluble guanylate cyclase (sGC), and phosphodiesterase-5 (PDE-5) are overexpressed, leading to decreased cyclic guanosine-monophosphate (cGMP). This results in constriction of hepatic sinusoids, contributing about 30% of portal pressure. In contrast, in peripheral arteries, dilation prevails with excess cGMP due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 126 publications
(186 reference statements)
2
13
0
Order By: Relevance
“…Cirrhotic patients with and without CSPH were of comparable age and gender distribution with a median age of 60 (55-67) and 61 (54-67) years (p = 0.925) and a majority of 49 (70.0%) and 15 (71.4%) males, respectively (p = 0.900). As to be expected, patients with CSPH had more advanced liver disease, highlighted by a MELD score of 11(8)(9)(10)(11)(12)(13)(14) in comparison to patients without CSPH with a MELD score of 7 (7-8; p = 0.007). Alcoholic liver disease was the leading etiology in patients with CSPH (n = 45, 64.3 %), while cirrhotic patients without CSPH mostly had viral liver disease (n = 15, 71.4 %).…”
supporting
confidence: 68%
See 2 more Smart Citations
“…Cirrhotic patients with and without CSPH were of comparable age and gender distribution with a median age of 60 (55-67) and 61 (54-67) years (p = 0.925) and a majority of 49 (70.0%) and 15 (71.4%) males, respectively (p = 0.900). As to be expected, patients with CSPH had more advanced liver disease, highlighted by a MELD score of 11(8)(9)(10)(11)(12)(13)(14) in comparison to patients without CSPH with a MELD score of 7 (7-8; p = 0.007). Alcoholic liver disease was the leading etiology in patients with CSPH (n = 45, 64.3 %), while cirrhotic patients without CSPH mostly had viral liver disease (n = 15, 71.4 %).…”
supporting
confidence: 68%
“…Various studies in the animal model of portal hypertension have demonstrated decreased hepatic cGMP activity with reflectively increased splanchnic and systemic cGMP activity ( 4 7 ). These alterations are believed to be a major contributing factor to the state of profuse hepatic vascular resistance and hyperdynamic splanchnic and systemic circulation that characterizes cirrhotic portal hypertension ( 12 , 13 ). This pathophysiological background suggests that cGMP could be a biomarker of portal hypertension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PDE5 is an enzyme which converts vasodilating cGMP into its inactive form and is increased in the cirrhotic liver. Its modulation using PDE5-inhibitors may have potential in the treatment of ACLD, as highlighted in a recent review [ 155 ]. In the clinical setting, results have been mixed, with some studies showing no change in HVPG [ 59 , 156 ], while others observed a decrease [ 41 , 60 ].…”
Section: Therapeutic Agents For Liver Cirrhosis and Portal Hypertensionmentioning
confidence: 99%
“…The latter (i.e., sildenafil, vardenafil, tadalafil,) are mostly known for their clinical use in the treatment of erectile dysfunction [ 54 ]. They are also applied in other diseases, such as male lower urinary tract symptoms (LUTS), psoriasis arthritis, nonalcoholic fatty liver disease (NAFLD), liver cirrhosis, pulmonary arterial hypertension (PAH) [ 55 , 56 , 57 , 58 , 59 , 60 ]. Nevertheless, these compounds, alone or in combination with chemotherapeutics, have been heralded as promising drugs for the treatment of several malignancies, including breast cancer, although their role is yet to be fully clarified [ 61 , 62 , 63 , 64 ].…”
Section: Challenges Of Targeting Cgmp Signaling In Breast Cancermentioning
confidence: 99%